2018
DOI: 10.3389/fpubh.2018.00292
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Burden of Malnutrition Increases the Risk of Cesarean Delivery: Evidence From India

Abstract: Background: Among contemporary human populations, rates of cesarean delivery vary substantially, making it difficult to know if the procedure is inadequately available, or used excessively relative to medical need. A much-cited evolutionary hypothesis attributed birth complications to an “obstetric dilemma,” resulting from antagonistic selective pressures acting on maternal pelvic dimensions and fetal brain growth during hominin evolution. However, the childbirth challenges experienced by living humans may not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 47 publications
(59 reference statements)
5
40
1
1
Order By: Relevance
“…Several factors have been associated with high rates of CS. It has been showed that the dual burden of malnutrition -the coexistence of short stature and overweight/obesity-exacerbate obstetric complications through influences on maternal phenotype and new-born size (Wells, Wibaek, & Poullas, 2018). Almost 63% of mothers of this sample exhibited short stature and high BMI.…”
Section: Discussionmentioning
confidence: 88%
“…Several factors have been associated with high rates of CS. It has been showed that the dual burden of malnutrition -the coexistence of short stature and overweight/obesity-exacerbate obstetric complications through influences on maternal phenotype and new-born size (Wells, Wibaek, & Poullas, 2018). Almost 63% of mothers of this sample exhibited short stature and high BMI.…”
Section: Discussionmentioning
confidence: 88%
“…Overweight and obesity raise the risk of macrosomic offspring, increasing the risk of fetomaternal disproportion and obstructed labor. Indeed, a recent study found that Indian women who were both short and overweight were more likely to have a cesarean delivery than women who were either short or overweight alone (Wells, Wibaek, & Poullas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should seek to characterize the developmental trajectory of different pelvic dimensions and also investigate the potential impacts of early‐life nutritional interventions (eg, those aimed at reducing stunting) on adult pelvis size and shape. It will be important to focus efforts on reversing negative secular trends in height, especially in populations where maternal BMI is increasing (Wells et al, ). This can be achieved by improving success in the prevention of early linear growth faltering and stunting.…”
Section: Discussionmentioning
confidence: 99%
“…For obstetricians, our hypothesis may appear unintuitive because many previous studies documented that-at an individual level-taller women have lower, not higher, rates of obstructed labour [7,11,14,46]. However, we propose thatat a population level-the intergenerational change of body size, not only current body size, affects obstructed labour: the faster the environmentally induced increase in body size, the more frequent is fetopelvic disproportion.…”
Section: Introductionmentioning
confidence: 75%